Dimensional comparisons: How academic track students’ achievements are related to their expectancy and value beliefs across multiple domains - Gaspard, Hanna; Wigfield, Allan; Jiang, Yi; Nagengast, Benjamin; Trautwein, Ulrich; Marsh, Herb W. (Contemporary educational psychology, 2018)
•Expectancies, values, and achievements were assessed in five academic domains.•Expectancies and most value facets showed high degrees of domain-specificity.•Students engaged in contrasting and assimilative comparisons across domains.•Such processes were evident for paths from achievements to expectancies and values.•Dimensional comparisons were weaker for utility value facets. In the present study, we investigated how students’ expectancies and values can be predicted by their achievements in multiple domains. Our major aim was to extend previous findings on dimensional comparison processes for expectancies to task values while systematically comparing multiple value facets defined in expectancy-value theory. We assessed the expectancies, values, and achievements of N = 857 students in Grades 5–12 from two German academic track schools in five academic domains. The results for students’ expectancies largely supported the predictions that were derived from dimensional comparison theory: We found strong evidence for negative cross-domain paths between achievements and expectancies in “far” domains such as math and languages, indicating contrast effects. There were also some positive cross-domain paths between achievements and expectancies in “near” domains such as math and physics, indicating assimilation effects. We also found similar patterns of cross-domain paths for students’ values. However, the results varied substantially across the nine value facets under investigation. We found the strongest evidence for dimensional comparison processes for the value facets most closely related to expectancy (e.g., intrinsic value and cost facets), whereas we found only a little evidence for dimensional comparison processes for the facets of utility value.